MENGANALISIS PRILAKU GENERASI Z PADA PEMILU 2024 - Idawati; Padila; Saipul Anwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the political behavior of Generation Z in the context of the 2024 General Election (Pemilu) around the State Islamic University (UIN) Raden Fatah Palembang. Generation Z, generally born between 1997 and 2012, represents the age group that has begun to actively participate in formal political processes and became the largest segment of voters in the 2024 election. This phenomenon is particularly interesting to examine because the political behavior of this generation differs significantly from that of previous generations. With their high exposure to technology, fast access to information, and intense use of social media, Generation Z’s political attitudes and decisions are often influenced by digital dynamics, social identity, and a growing critical awareness of political, economic, and social issues.This research employs a qualitative descriptive approach, using methods such as observation, in-depth interviews, and documentation. The research informants consist of active UIN Raden Fatah Palembang students categorized as Generation Z who participated in the 2024 election. Data were collected using purposive sampling, considering variations in social backgrounds, organizational involvement, and levels of political understanding. Data analysis was conducted through data reduction, data display, and conclusion drawing to identify behavioral patterns and political tendencies among the respondents.The findings reveal that the political behavior of Generation Z around UIN Raden Fatah Palembang is characterized by rational and pragmatic orientations, yet still influenced by emotional and digital identity factors. Most respondents demonstrate interest in national political issues; however, their participation tends to occur more in the realm of digital politics through social media platforms such as Instagram, TikTok, and X (Twitter). This generation tends not to be bound to specific ideologies or political parties; instead, they evaluate candidates based on personal image, track record, and media representation. On the other hand, their involvement in direct political activities—such as attending campaigns or volunteering for political parties—remains relatively low due to apathy toward practical politics and a lack of trust in political elites.Moreover, this study finds that political education within the university environment plays a crucial role in shaping Generation Z’s critical awareness. Classroom discussions, student organizations, and academic activities serve as potential spaces for enhancing political literacy. However, the low intensity of constructive political dialogue and the scarcity of exemplary public leadership limit the development of substantive political participation. Despite these challenges, there is a positive trend showing that Generation Z is increasingly inclined to become agents of change through social actions and digital advocacy, representing a form of non-conventional political participation.Overall, the political behavior of Generation Z around UIN Raden Fatah Palembang during the 2024 election reflects a transformation of political orientation from conventional models toward more participatory and digital-based forms. This generation holds great potential to become a critical, creative, and adaptive political force—provided that they receive continuous political education, ethical digital literacy, and are supported by a transparent political system. Therefore, this study contributes to a broader understanding of the dynamics of youth political behavior in the digital era and emphasizes the importance of educational institutions in cultivating democratic political character among Indonesia’s younger generation.